Orthosiphon stamineus Benth. (Lamiaceae): a bibliometric analysis of its antidiabetic properties - Nneka Augustina Akwu; Folasade Banji-Onisile; Adeoye John Kayode; Unarine Rambau; Melisa Mendez; Ijeoma Nnadozie; Arif Nur Muhammad Ansori; Hery Purnobasuki (Acta Scientiarum. Biological Sciences, 2025)
The use of medicinal plants for the management of diabetes is gaining rapid attention. There are several reports on the antidiabetic properties of Orthosiphon stamineus Benth. There has been no previous bibliometric analysis review conducted on O. stamineus as an antidiabetic agent to date. Therefore, this review is centred on gathering information about the potential sources of antidiabetic properties from O. stamineus. A bibliometric analysis on the antidiabetic properties of O. stamineus was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Scientific publications in the SCOPUS database were retrieved using the search strings ‘Orthosiphon stamineus’ OR ‘Orthosiphon aristatus’ OR ‘Kumis Kucing’ OR ‘Misai Kucing’ OR ‘Java tea’ AND ‘diabetes’ OR ‘diabetes mellitus’ OR ‘dm’ OR ‘antidiabetic’ OR ‘hypoglycemic’ OR ‘diabetic complications’ OR ‘insulin’ OR ‘glucose’. 76 articles related to O. stamineus and diabetes were included after the exclusion criteria. The bibliometric analysis spanning from 1991 and 2023 sheds light on the dynamic and collaborative research landscape surrounding O.stamineus. It highlights several aspects of the plant's multifaceted exploration for potential antidiabetic properties, including a surge in activity in 2006 and 2012, international contributions, a diverse distribution across journals, and a broad spectrum of keyword concepts.